Microfilaria in malignant pleural effusion: an unusual incidental finding or causative association? - Chordiya, Anandkumar P.; Datar, Sonali S.; Agrawal, Amit K.; Gadkari, Rasika U.; Shrikhande, Anuradha V. (International Journal of Research in Medical Sciences, 2017)
Lymphatic filariasis is common in tropical countries and is endemic in India. Filaria has a wide spectrum of presentation. Filarial lung involvement is usually in the form of tropical pulmonary eosinophilia with pulmonary infiltrates and peripheral eosinophilia. Filariasis presenting with pleural effusion is an unusual presentation. Malignancy in association with filarial pleural effusion is extremely rare and its role in tumorigenesis is controversial. In this context, we hereby report a case of 60 year old male, chronic smoker, who presented with left sided chest pain, cough, breathlessness, generalized weakness and swelling over left infrascapular region. Pleural fluid cytology repeated thrice due to degenerative changes, finally revealed malignant cells along with microfilaria. FNAC from left infrascapular swelling showed cytological features suggestive of metastatic deposits of Adenocarcinoma.